Anti-UV aging PPR material and PPR glass fiber weather-resistant composite pipe
By using sintered nanotitanium dioxide and tertiary hydroxide gel, combined with coupling agent and polyol phosphate, the problem of PPR pipes being prone to aging outdoors is solved, significantly improving the resistance to UV and stretching. yield stress.
Patent Information
- Application Number
- CN202411608740.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-14
AI Technical Summary
PPR pipes are susceptible to ultraviolet radiation in outdoor environments, resulting in a shortening of service life. In the prior art, there is an upper limit on the amount of masking agent added, which affects the anti-static pressure performance.
Using a masking agent made of nanotitanium dioxide and aluminum hydroxide gel sintering, nano-scale depressions and convex peaks are formed by alkali washing, increasing specific surface area and surface strength, and the modification coupling agent and polyol phosphate are enhanced compatibility. .
It significantly improves the UV aging resistance and tensile yield stress of PPR materials, and extends the outdoor service life of the pipe.
Smart Images

Figure BDA0005130370350000061 
Figure BDA0005130370350000071
Abstract
Description
Technical Field
[0001] The present application relates to water supply and drainage pipeline materials, and in particular to a UV-resistant PPR material and a PPR glass fiber weather-resistant composite pipe. Background Art
[0002] PPR pipe, also known as tri-propylene polypropylene pipe or random copolymer polypropylene pipe, is widely used in building water supply and drainage, agricultural irrigation. At present, PPR pipe has been improved to a multi-layer pipe, the innermost layer and the outermost layer are PPR materials without glass fiber addition and modification, and the middle layer is PPR material with glass fiber addition and modification. The middle layer provides good static pressure resistance for PPR pipe; the inner layer material has low additive leakage and is safer to contact with water directly, and the outer layer provides appearance and smooth outer surface of the pipe.
[0003] PPR pipes are easily aged, discolored, and brittle due to ultraviolet radiation when they are located outdoors in an uncovered state and in direct sunlight. Current technology allows the addition of shielding agents such as titanium dioxide and nano-silicon dioxide to PPR materials to shield ultraviolet rays. The shielding effect is related to the amount of shielding agent added. The more shielding agent is added, the better the shielding effect. However, there is an upper limit to the amount of shielding agent added. Adding too much will cause the tensile yield stress of PPR to decrease, resulting in the static pressure resistance of the pipe to become. Therefore, there are limitations on the improvement of anti-ultraviolet aging performance. The outdoor service life of PPR pipes is still greatly affected by ultraviolet radiation. Summary of the invention
[0004] In order to extend the service life of PPR pipes in uncovered conditions such as outdoors, a UV-resistant PPR material and a PPR glass fiber weather-resistant composite pipe are provided.
[0005] The above first invention objective of the present invention is achieved through the following technical solutions: A UV aging resistant PPR material, comprising the following raw materials: 100 parts of PPR, 10 to 14 parts of light calcium carbonate, and 30 to 38 parts of a screening agent; The particle size of the shielding agent is 100-200 nm, and the preparation method of the shielding agent is as follows: The nano titanium dioxide and aluminum hydroxide gel are mixed evenly and spray granulated to obtain a first material; The first material is pressed into a shape, and sintered at 1000-1150° C. to obtain a sintered body; The sintered body is crushed, ball-milled, the slurry is filtered, and sieved to obtain a second material with a particle size of 100 to 200 nm. The second material is in [OH - ] The masking agent is obtained by stirring and soaking in an alkali solution with a concentration of 0.1 to 0.12 mol / L, filtering and drying.
[0006] By adopting the above technical scheme, nano titanium dioxide and aluminum hydroxide gel are sintered densely at 1000-1150°C. In this process, aluminum hydroxide is dehydrated and converted into aluminum oxide, and the aluminum oxide is mixed with α and γ crystal forms. After alkali washing, the γ-type aluminum oxide is dissolved by alkali, so that a large number of nanometer-scale depressions and peaks are formed on the surface of the shielding agent. These depressions and peaks are composed of densely combined titanium dioxide and α-type aluminum oxide, which increases the specific surface area of the shielding agent. In addition, these nanometer-scale depressions and peaks increase the surface electron holes of the shielding agent, promote the activation of nano titanium dioxide, and better absorb ultraviolet rays. Therefore, the shielding agent has a large specific surface area and high surface strength, can form a high-strength bond with the organic phase, and relies on the shielding of the shielding agent material and the absorption of ultraviolet rays by titanium dioxide in the shielding agent to significantly improve the anti-UV aging performance of the PPR material.
[0007] Optional: The particle size of the nano titanium dioxide is 15±1 nm.
[0008] By adopting the above technical solution, the obtained shielding agent has a large specific surface area and a dense structure, and the PPR material has excellent tensile yield stress and anti-UV aging performance.
[0009] Optionally, the first material is obtained by uniformly mixing nano titanium dioxide, aluminum hydroxide gel, water and polyethylene glycol 400 in a mass ratio of 10: (11-13.2): (35-40): (0.2-0.34) and spray granulating.
[0010] By adopting the above technical scheme, nano titanium dioxide, aluminum hydroxide gel, water and polyethylene glycol are mixed into a slurry. Under the action of polyethylene glycol, the nano titanium dioxide and aluminum hydroxide gel are mixed more evenly, so that the distribution of titanium dioxide and aluminum oxide in the shielding agent obtained is more uniform, the obtained shielding agent has a higher bonding strength with the organic phase and a better absorption effect for ultraviolet rays, and the obtained PPR material has better tensile yield stress and UV resistance.
[0011] Optionally: the particle size of the first material is 15±5 μm.
[0012] By adopting the above technical scheme, the sintered body obtained by sintering is denser, the dense phase composed of titanium dioxide and α-alumina in the shielding agent obtained after crushing has higher strength, the surface of the shielding agent combined with the organic compound is not easy to break, the bonding strength is higher, and the tensile yield stress of the obtained PPR material is greater.
[0013] Optionally: the shielding agent is surface-modified by a coupling agent.
[0014] By adopting the above technical solution, the compatibility of the shielding agent with PPR is improved, thereby improving the uniformity of dispersion of the shielding agent in the PPR material, and then improving the tensile yield stress and UV resistance of the PPR material.
[0015] Optionally: the coupling agent is isopropyl titanate triisostearate.
[0016] By adopting the above technical scheme, isopropyl triisostearate titanate is a four-coordinated titanate coupling agent, which has higher binding activity with the shielding agent, higher modified adhesion rate, and better effect on improving the compatibility of the shielding agent.
[0017] Optionally, the polyol phosphate ester is also included in an amount of 2.2 to 3.2 parts.
[0018] By adopting the above technical solution, the γ-alumina is corroded after the shielding agent is alkaline washed, and depressions are formed on the surface of the shielding agent, so it has a large number of electron holes, and there are many free hydroxyl groups on the surface with high activity. Polyol phosphate can react with it, effectively enhancing the compatibility of the shielding agent, and then increasing the upper limit of shielding agent addition while ensuring strength, further improving the anti-UV effect of PPR materials.
[0019] The above second invention objective of the present invention is achieved through the following technical solutions: A PPR glass fiber weather-resistant composite pipe comprises an inner layer, a middle layer and an outer layer from the inside to the outside, wherein the middle layer is a glass fiber modified PPR material, and the outer layer is the UV aging resistant PPR material according to any one of claims 1 to 7.
[0020] By adopting the above technical solution, the outer layer material of the PPR pipe of the present application has both good strength and significant UV resistance, which makes the PPR pipe have a longer service life in outdoor environments.
[0021] In summary, this application has at least the following beneficial effects: 1. The shielding agent is composed of uniformly distributed and dense titanium dioxide and aluminum oxide. It has a large specific surface area and high surface strength. It can form a high-strength bond with the organic phase. It relies on the shielding of the shielding agent material and the absorption of ultraviolet rays by titanium dioxide in the shielding agent to significantly improve the anti-UV aging performance of the PPR material; 2. By modifying the titanate coupling agent and enhancing the compatibility with polyol phosphate, the shielding agent is more evenly dispersed in the PPR material, which significantly improves the tensile yield stress and UV resistance of the PPR; 3. The outer layer material of the PPR pipe of the present application has both good strength and significant UV resistance, which makes the PPR pipe have a longer service life in outdoor environments. DETAILED DESCRIPTION
[0022] raw material Nano titanium dioxide is a commercially available product. According to the particle size, there are three specifications of raw materials: 15±1nm nano titanium dioxide, 2±0.5nm nano titanium dioxide, and 50±1nm nano titanium dioxide.
[0023] The aluminum hydroxide gel is self-made, and the preparation method is as follows: prepare a 0.28 mol / L chromium chloride solution with aluminum chloride as a raw material, slowly add ammonia water to the solution, adjust the pH value to 11-12, and stir for 2-5 hours to produce aluminum hydroxide gel, and repeatedly rinse the prepared aluminum hydroxide gel with high-purity water, drain the water and adjust the water content to 20±0.5wt%, to obtain aluminum hydroxide gel. The amount of aluminum hydroxide gel used in subsequent use is measured based on the actual amount of aluminum hydroxide. The amount of aluminum hydroxide gel used = the amount of aluminum hydroxide gel weighed * (1-water content).
[0024] Isopropyl titanate triisostearate, n-octyltriethoxysilane, polyethylene glycol 400, sodium hydroxide, aluminum chloride, and ethanol are all commercially available products with a purity of more than 99%.
[0025] The PPR is PPR 12236 product commercially available from Dorda.
[0026] Light calcium carbonate is a commercially available product with a particle size of 1±0.5 μm.
[0027] The polyol phosphate is PAPE (CAS: 6419-19-8), a commercial product of Shandong Xinghai Chemical Co., Ltd., with a concentration of 50 wt %. The amount used is based on the actual amount of the polyol phosphate.
[0028] Preparation Example 1 A screening agent, the preparation method of which is as follows: 15±1 nm nano titanium dioxide, aluminum hydroxide gel, water, and polyethylene glycol 400 are uniformly mixed in a mass ratio of 10:12.5:38:0.26, spray granulated, and particles with a particle size of 15±5 μm are screened to obtain a first material; The first material is pressed into a shape under an isostatic pressure of 2.8 MPa, and sintered at 1150° C. to obtain a sintered body; The sintered body is then crushed, ball-milled, slurry filtered, and sieved to obtain a second material with a particle size of 150 nm. The second material was put into a 0.1 mol / L sodium hydroxide solution and stirred and soaked for 1 hour. The mass ratio of the second material to the sodium hydroxide solution was 1:8. After the soaking, it was filtered and dried to obtain a shielding agent.
[0029] Preparation Example 2 A shielding agent, which is different from Preparation Example 1 in that the sintering temperature of the sintered body is 1000°C.
[0030] Preparation Example 3 A shielding agent, which is different from Preparation Example 1 in that the particle size of nano titanium dioxide is 2±0.5 nm.
[0031] Preparation Example 4 A shielding agent, which is different from Preparation Example 1 in that the particle size of nano titanium dioxide is 50±1 nm.
[0032] Preparation Example 5 A shielding agent, which differs from Preparation Example 1 in that the first material is obtained differently. The first material is obtained as follows: 15±1nm nano titanium dioxide, aluminum hydroxide gel, and water are mixed and stirred at a mass ratio of 10:12.5:38, spray granulated, and particles with a particle size of 15μm are screened to obtain the first material.
[0033] Preparation Example 6 A shielding agent, which is different from Preparation Example 1 in that the particle size of the first material obtained by spray granulation and screening is 2±1 μm.
[0034] Preparation Example 7 A shielding agent, which is different from Preparation Example 1 in that the particle size of the first material obtained by spray granulation and screening is 100±1 μm.
[0035] Preparation Example 8 A shielding agent is further improved on the basis of Preparation Example 1, as follows.
[0036] The shielding agent obtained in Preparation Example 1 is added to the modified solution, which is a mixture of isopropyl titanate triisostearate, ethanol and water in a mass ratio of 10:24:6, and the mass ratio of the shielding agent to the modified solution is 1:7.6. After mixing and stirring evenly, let it stand for 12 hours, filter and dry to obtain the shielding agent of Preparation Example 7.
[0037] Preparation Example 9 A shielding agent, which is different from Preparation Example 8 in that the modified solution is a mixture of n-octyltriethoxysilane, ethanol and water in a mass ratio of 10:30:6.
[0038] Comparative Preparation Example 1 A shielding agent, which is different from Preparation Example 1 in that the firing temperature of the sintered body is 1300°C.
[0039] Comparative Preparation Example 2 A shielding agent, which is different from Preparation Example 1 in that the firing temperature of the sintered body is 900°C.
[0040] Comparative Preparation Example 3 A shielding agent, wherein the second material prepared in Preparation Example 1 is directly used as the shielding agent.
[0041] Example 1 A UV aging resistant PPR material, whose raw materials are PPR, light calcium carbonate, a screening agent and polyol phosphate.
[0042] The shielding agent is prepared in Preparation Example 1.
[0043] The preparation method is as follows: 100 kg of PPR, 13.2 kg of light calcium carbonate, 36.4 kg of a masking agent, and 3 kg of polyol phosphate are uniformly mixed, and then put into a screw extruder for melt extrusion.
[0044] Example 2 A PPR material resistant to UV aging, which is different from Example 1 in that the shielding agent is prepared in Preparation Example 2.
[0045] Example 3 A PPR material resistant to UV aging, which differs from Example 1 in that the shielding agent is prepared in Preparation Example 3.
[0046] Example 4 A PPR material resistant to UV aging, which differs from Example 1 in that the shielding agent is prepared in Preparation Example 4.
[0047] Example 5 A PPR material resistant to UV aging, which differs from Example 1 in that the shielding agent is prepared in Preparation Example 5.
[0048] Example 6 A PPR material resistant to UV aging, which differs from Example 1 in that the shielding agent is prepared in Preparation Example 6.
[0049] Example 7 A PPR material resistant to UV aging, which differs from Example 1 in that the shielding agent is prepared in Preparation Example 7.
[0050] Example 8 A PPR material resistant to UV aging, which differs from Example 1 in that the shielding agent is prepared in Preparation Example 8.
[0051] Example 9 A PPR material resistant to UV aging, which differs from Example 1 in that the shielding agent is prepared in Preparation Example 9.
[0052] Example 10 A UV aging resistant PPR material, which is different from Example 1 in that the amount of polyol phosphate used is 0.
[0053] Embodiment 11 A UV aging resistant PPR material, which differs from Example 8 in that the amount of raw materials used is different, specifically: 100kg PPR, 10kg light calcium carbonate, 30kg screening agent, and 2.2kg polyol phosphate.
[0054] Example 12 A UV aging resistant PPR material, which differs from Example 8 in that the amount of raw materials used is different, specifically: 100kg PPR, 14kg light calcium carbonate, 38kg screening agent, and 3.2kg polyol phosphate.
[0055] Comparative Example 1 A PPR material, which is different from Example 1 in that the shielding agent is prepared by Comparative Preparation Example 1.
[0056] Comparative Example 2 A PPR material, which is different from Example 1 in that the shielding agent is prepared by Comparative Preparation Example 2.
[0057] Comparative Example 3 A PPR material, which is different from Example 1 in that the shielding agent is prepared according to Comparative Preparation Example 3.
[0058] Comparative Example 4 A PPR material, which is different from Example 1 in that the shielding agent is 15±1 nm nano titanium dioxide.
[0059] Detection The initial tensile yield stress of the PPR materials obtained in Examples 1 to 12 and Comparative Examples 1 to 4 was tested, and the same sample was subjected to an aging test according to Method A in Table 4 of GB / T16422.3-2022, cycle number 1. The tensile yield stress was tested again after a test time of 2000 h, and the tensile yield stress retention rate after aging was calculated.
[0060] Table 1. Test results of Examples 1 to 12 and Comparative Examples 1 to 4 Combined with Table 1, comparing Examples 1 to 2 with Comparative Examples 1 to 4, the initial tensile yield stress of Examples 1 to 2 is significantly better than that of Comparative Examples 1 to 3, and the tensile yield stress retention rate after aging is significantly better than that of Comparative Examples 1 to 3. This is because the shielding agent of Examples 1 to 2 is obtained by sintering, crushing and alkali washing of nano-titanium dioxide and aluminum hydroxide gel at 1000 to 1150°C. The aluminum oxide converted by sintering the aluminum hydroxide gel at 1000 to 1150°C has both α and γ crystal forms. After alkali washing, the γ-type aluminum oxide is dissolved by alkali, so that a large amount of The nanometer-scale depressions and peaks are composed of densely bound titanium dioxide and α-alumina, which increase the specific surface area of the shielding agent and increase the surface strength. In addition, these nanometer-scale depressions and peaks increase the surface electron holes on the shielding agent, promote the activation of nano-titanium dioxide, and better absorb ultraviolet rays. Therefore, the shielding agent has a large specific surface area and high surface strength, can form a high-strength bond with the organic phase, and rely on the shielding of the shielding agent material and the absorption of ultraviolet rays by titanium dioxide in the shielding agent to significantly improve the UV aging resistance of the PPR material in Example 1.
[0061] In Comparative Example 1, the firing temperature of the shielding agent is too high, and the aluminum hydroxide is converted into α-type aluminum oxide, which does not dissolve during the alkali washing process; in Comparative Example 2, the firing temperature of the shielding agent is too low, and the aluminum hydroxide is only converted into γ-type aluminum oxide, which is dissolved in large quantities during the alkali washing process, and the grooves and peaks formed are too large, the electron hollowness does not increase, and the surface strength is reduced; Comparative Example 3 is not alkali washed, and no large number of nanometer-scale depressions and peaks are formed; therefore, the shielding agents used in Comparative Examples 1 to 3 cannot enhance the UV resistance and initial tensile yield stress of the PPR material as well as the shielding agents used in Examples 1 to 2.
[0062] Comparative Example 4 uses a single titanium dioxide as a shielding agent, the amount of shielding agent used is relatively large, the bonding strength with the organic phase is far less than that of the shielding agent in Example 1, and there is no enhanced ultraviolet absorption effect brought by the nano-scale depressions and peaks in Example 1. Therefore, the shielding agent used in Comparative Example 4 cannot enhance the anti-UV performance and initial tensile yield stress of the PPR material as well as the shielding agent used in Examples 1 to 2.
[0063] Comparing Example 1 with Examples 3 to 4, it can be seen that the difference between the three is that the particle size of the nano-titanium dioxide used in the preparation of the shielding agent is different. The particle size of nano-titanium dioxide affects the distribution of alumina and titanium dioxide during the sintering process of the shielding agent, and thus the particle size of nano-titanium dioxide affects the surface bonding strength between the shielding agent and the organic phase and the UV resistance of the shielding agent. Combined with the test results, the initial tensile yield stress and the tensile yield stress retention rate after aging of Example 1 are better than those of Examples 3 to 4. In this application, the nano-titanium dioxide preferably has a particle size of 15±1nm.
[0064] In addition, the mixing and dispersion of nano-titanium dioxide and aluminum hydroxide gel during the preparation of the shielding agent and the particle size of the first material both affect the distribution of nano-titanium dioxide and aluminum oxide in the sintered body.
[0065] In combination with Example 1 and Example 5, the initial tensile yield stress and the retention rate of the tensile yield stress after aging of Example 1 are better than those of Example 5. Therefore, the addition of polyethylene glycol when the nano-titanium dioxide and aluminum hydroxide gel are mixed and dispersed in the present application can make the distribution of titanium dioxide and aluminum oxide in the shielding agent more homogeneous, and the resulting shielding agent has a higher bonding strength with the organic phase and a better absorption effect on ultraviolet rays, and the resulting PPR material has better tensile yield stress and UV resistance.
[0066] In combination with Example 1 and Examples 6 to 7, the initial tensile yield stress and the retention rate of the tensile yield stress after aging of Example 1 are better than those of Examples 6 to 7. In the present application, the particle size of the first material is preferably selected to be 15±5 μm. The sintered body obtained by sintering is denser, and the dense phase composed of titanium dioxide and α-alumina in the shielding agent obtained after crushing has higher strength. The surface of the shielding agent combined with the organic compound is not easy to break, and the bonding strength is higher. The tensile yield stress of the obtained PPR material is greater.
[0067] The present application also further improves the shielding agent used in Example 1 to enhance the compatibility of the shielding agent, such as using a coupling agent to modify the shielding agent in Examples 8 to 9. The initial tensile yield stress and the retention rate of the tensile yield stress after aging of Examples 8 to 9 are better than those of Example 1, and the initial tensile yield stress and the retention rate of the tensile yield stress after aging of Example 8 are better than those of Example 9. It can be seen that the shielding agent in the present application is treated with a coupling agent surface modification, which can improve the uniformity of the dispersion of the shielding agent in the PPR material, and then improve the tensile yield stress and UV resistance of the PPR material, among which isopropyl titanate triisostearate has a better effect.
[0068] By comparing Example 1 and Example 10, it can be seen that the PPR material of the present application also adds polyol phosphate. The free hydroxyl groups on the surface of the shielding agent are numerous and highly active. The polyol phosphate can react with it, effectively enhancing the compatibility of the shielding agent, and then increasing the upper limit of the shielding agent addition while ensuring the strength, further improving the UV resistance of the PPR material. Therefore, the initial tensile yield stress and the tensile yield stress retention rate after aging of Example 1 are better than those of Example 10.
[0069] Combined with other preferred examples of the present application - Examples 11 to 12, the initial tensile yield stress and the retention rate of the tensile yield stress after aging of Examples 11 to 12 are significantly better than those of Comparative Examples 1 to 3. Therefore, when the mass ratio of PPR, light calcium carbonate, shielding agent, and polyol phosphate in the raw materials of the PPR material of the present application is controlled to be 100: (10 to 14): (30 to 38): (2.2 to 3.2), the PPR material of the present application can obtain excellent anti-UV aging performance while ensuring good tensile yield stress.
[0070] Embodiment 13 A PPR glass fiber weather-resistant composite pipe includes an inner layer, an intermediate layer and an outer layer from the inside to the outside. The intermediate layer is a glass fiber modified PPR material, and the outer layer is a UV aging resistant PPR material. The UV aging resistant PPR material is one of Examples 1 to 12.
[0071] The outer layer material of the PPR pipe of the present application has both good strength and significant UV resistance, which makes the PPR pipe have a longer service life in outdoor environments.
[0072] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as the modifications are within the scope of protection required by the present application, they shall be protected by the patent law.
Claims
1. A UV aging resistant PPR material, characterized in that: It includes the following raw materials: 100 parts of PPR, 10-14 parts of light calcium carbonate, and 30-38 parts of shielding agent; The particle size of the shielding agent is 100-200 nm, and the preparation method of the shielding agent is as follows: The nano titanium dioxide and aluminum hydroxide gel are mixed evenly and spray granulated to obtain a first material; The first material is pressed into a shape, and sintered at 1000-1150° C. to obtain a sintered body; The sintered body is crushed, ball-milled, the slurry is filtered, and sieved to obtain a second material with a particle size of 100-200 nm. The second material is in [OH - ] The masking agent is obtained by stirring and soaking in an alkali solution with a concentration of 0.1-0.12 mol / L, filtering and drying.
2. The UV-resistant PPR material according to claim 1, characterized in that: The particle size of the nano titanium dioxide is 15±1 nm.
3. The UV-resistant PPR material according to claim 1, characterized in that: The first material is obtained by uniformly mixing nano titanium dioxide, aluminum hydroxide gel, water and polyethylene glycol 400 in a mass ratio of 10: (11-13.2): (35-40): (0.2-0.34) and spray granulation.
4. The UV-resistant PPR material according to claim 3, characterized in that: The particle size of the first material is 15±5 μm.
5. The UV-resistant PPR material according to claim 1, characterized in that: The shielding agent is surface-modified by a coupling agent.
6. The UV-resistant PPR material according to claim 4, characterized in that: The coupling agent is isopropyl titanate triisostearate.
7. The UV-resistant PPR material according to claim 1, characterized in that: It also includes 2.2 to 3.2 parts of the polyol phosphate.
8. A PPR glass fiber weather-resistant composite pipe, characterized in that: From the inside to the outside, it includes an inner layer, a middle layer and an outer layer, the middle layer is a glass fiber modified PPR material, and the outer layer is the UV aging resistant PPR material according to any one of claims 1 to 7.